2021
DOI: 10.1136/bmj.n776
|View full text |Cite
|
Sign up to set email alerts
|

Role of coronary artery calcium score in the primary prevention of cardiovascular disease

Abstract: First developed in 1990, the Agatston coronary artery calcium (CAC) score is an international guideline-endorsed decision aid for further risk assessment and personalized management in the primary prevention of atherosclerotic cardiovascular disease. This review discusses key international studies that have informed this 30 year journey, from an initial coronary plaque screening paradigm to its current role informing personalized shared decision making. Special attention is paid to the prognostic value of a CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 153 publications
0
41
0
3
Order By: Relevance
“…CAC scoring is reliable, and its reproducibility has been extensively studied across different CT imaging modalities [18] , [30] , [31] , [32] , [33] . Numerous studies have found that the CAC score is meaningful and recommended for consideration in the risk stratification for coronary heart disease and atherosclerotic cardiovascular disease [6] , [7] , [8] , [9] , [20] , [34] , [35] , [36] , [37] . In addition, the presence or absence of CAC is a powerful indicator and can be used as a negative risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAC scoring is reliable, and its reproducibility has been extensively studied across different CT imaging modalities [18] , [30] , [31] , [32] , [33] . Numerous studies have found that the CAC score is meaningful and recommended for consideration in the risk stratification for coronary heart disease and atherosclerotic cardiovascular disease [6] , [7] , [8] , [9] , [20] , [34] , [35] , [36] , [37] . In addition, the presence or absence of CAC is a powerful indicator and can be used as a negative risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence or absence of CAC is a powerful indicator and can be used as a negative risk factor. Studies have shown that even in populations classified as at high risk (e.g., with high levels of hs-CRP and high-risk factors such as dyslipidemia and smoking), those with the zero CAC score have a lower risk of atherosclerotic cardiovascular disease [34] . According to the updated guideline [35] , these patients could be reclassified to the low-risk group if CAC is not detected, and preventive interventions (e.g., statins) could be reasonably postponed.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Special attention is paid to a CAC score of zero (the so-called ‘power of zero’) which, in a specific setting, may influence management decisions with respect to excluding CAD or initiating preventive therapies such as statins. 59 …”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is the major pathophysiological basis of cerebrovascular and cardiovascular diseases and can be attributed to the interactions of a myriad of risk factors ( Wang et al, 2021a ; Qi et al, 2021 ; Xuan et al, 2021 ). With the increasing ageing population in most developed countries, the mortality and morbidity of cardiovascular and cerebrovascular diseases are growing worldwide ( Birger et al, 2021 ; Faggiano et al, 2021 ; Nasir and Cainzos-Achirica, 2021 ). Vascular smooth muscle cells (VSMCs) constitute the main structure of the vasculature and are key to the maintenance of vascular tone and blood pressure ( Zhang et al, 2014 ; Cil et al, 2021 ; Zhu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%